Pendampingan Memasarkan Produk Hasil Usaha UKM Melalui Penggunaan Media Sosial di Desa Cikumpay Kabupaten Purwakarta - Jalaludin, Jalaludin; Fauzy, Fahrurrohman; Nurapiah, Dewi; Apriani, Fitri (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this Community Service (PKM) activity is to improve the ability and skills of the marketing aspects of business products, especially those related to the ability and skills to make business product promotions using online media. The results of these tools will later be shared through chat applications on Social Media with Facebook, Instagram and web.whatsapp.com to improve and develop the business. So that it can expand the marketing area of ​​business products at a relatively faster and cheaper cost, even without any promotion costs at all. Implementation of PKM activities in Cikumpay Village, Kec. Campaka Kab. Purwakarta by involving 4 SMEs who are PKM Partners. The method of implementing the activity is by directly visiting the business location of each PKM partner for socialization, training, mentoring and discussion activities, as well as evaluation monitoring. The results showed that PKM Partners became skilled in promoting business products and could also promote through chat applications on social media on Facebook, Instagram and web.whatsapp.com.